Notice of Fragments of Sculptured Stones at the Church of Tealing, near Dundee: With a Supplementary Note on the Ingram of Kettins (Proceedings of the Society of Antiquaries of Scotland, 1911)
A monumental slab in memory of Ingram of Kettins, built into one of the interior walls, believed to furnish the earliest stone inscription in the Scottish vernacular and a fragment of a Celtic cross slab which had been utilised as a building stone in the outside of the south wall of the church are reported on. Both stones have been moved during church repairs. The cross slab is now found to have been sculptured on both sides. The reverse shows a fragment of the well-known figure of the beast with the long jaws and scroll feet'”the " elephant " of these sculptures. The panel enclosing this figure is bordered by a double enrichment of fret pattern, the outer one in rectangular order. This particular fret is rare in Scotland. A third stone which was part of an aumbry is also now displayed. It has much in common with the style of Ingram's monument.